BARAZANJI PADA KAMUNITAS ARA-BIRA KAB. BULUKUMBA (PERSPEKTIF SOSIOLOGI KOMUNIKASI) - Sakaruddin Mandjarreki (Jurnal Komodifikasi, 2017)
Rituality of barazanji is connotatively defined as the medium of transfer of moral values through interaction of duality, ie from the actor to the listener and the audience of historic speech. The admiration of the greatness of personality and the height of the morality of the Apostle is the main menu that is proclaimed. With that content so that barazanji readings can be accepted by every level of social stratification in the country until now. The simultaneous and progressive economic, social and cultural globalization of all civilizations in the world does not necessarily deconstruct this tradition from the trough of the consensus of the local community. The only clarified distortion is the reproductive delay of barazanji script memorization as the effect of globalization. The cluster of Ara and Bira village communities is a community that can not be isolated or even legitimized from the tradition of barzanji readings. Each life cycle is legitimized with a moral chant of barzanji.